A lockdown a day keeps the doctor away: The effectiveness of non-pharmaceutical interventions during the Covid-19 pandemic - Anthonin Levelu; Alexander-Nikolai Sandkamp (Kiel Institute for the World Economy (IfW Kiel), 2022)
Countries have employed a variety of non-pharmaceutical interventions (NPIs) in order to curtail the COVID-19 pandemic. However, the success of individual measures in reducing the number of infections remains controversial. This paper exploits a panel data set of 107 countries to estimate the effects of 14 NPIs on the spread of the disease. While almost all measures had a dampening effect on the reproduction rate of the virus, public information campaigns and school closings were most effective, followed by testing policies, contact tracing and international travel restrictions. Public event cancellation and school closings were less effective during the second wave of the pandemic, while public information campaigns and the obligation to wear masks worked better. Several NPIs had a stronger impact on infections in autocratic countries, while others were less effective.
Keywords: C1; C5; I1; 330; COVID-19; non-pharmaceutical interventions; policy analysis; panel data